2018
DOI: 10.1140/epjc/s10052-018-5874-1
|View full text |Cite
|
Sign up to set email alerts
|

Possible open-charmed pentaquark molecule $$\varOmega _c(3188)$$ Ω c ( 3188 ) – the

Abstract: We study the S-wave DΞ bound state in the Bethe-Salpeter formalism in the ladder and instantaneous approximations. With the kernel generated by the hadronic effective Lagrangian, two open-charmed bound states, which quantum numbers are I = 0, J P = (1 2) − and I = 1, J P = (1 2) − , respectively, are predicted as new candidates of hadronic pentaquark molecules in our formalism. If existing, they could contribute to the broad 3188 MeV structure near the five new narrow Ω c states observed recently by the LHCb C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Several other works [17,18,19,20] have also addressed the possibility of interpreting of some of the Ω c states seen at CERN as quasi-bound meson-baryon systems, as well as the prediction of analogous states in the bottom sector [21], finding results which are similar to those of our work [16] and hinting that the meson-baryon description cannot be ignored when trying to understand the nature of these excited heavy baryons.…”
Section: Discussionsupporting
confidence: 79%
“…Several other works [17,18,19,20] have also addressed the possibility of interpreting of some of the Ω c states seen at CERN as quasi-bound meson-baryon systems, as well as the prediction of analogous states in the bottom sector [21], finding results which are similar to those of our work [16] and hinting that the meson-baryon description cannot be ignored when trying to understand the nature of these excited heavy baryons.…”
Section: Discussionsupporting
confidence: 79%
“…In Ref. [50] the authors propose that the broad structure found around 3188 MeV [1,2] could be related with a molecular ΞD state due to the proximity of its threshold around 3185 MeV. As we shall see in the next section, in our approach [44] the molecular state dominated by the ΞD channel corresponds to the Ω c ð3090Þ.…”
Section: Introductionmentioning
confidence: 80%
“…The Ã Ξ are unlikely to bind, though their interaction is indeed attractive as can be deduced from their scattering lengths. As a consequence, the interpretation of the Ω c ð3188Þ enhancement as a DΞ bound state [39] is disfavored. The conclusion about a possible 3 2 − D Ã Ξ molecule is also different from Ref.…”
Section: Discussionmentioning
confidence: 99%
“…The LHCb data also hint at a structure around 3188 MeV, which is near the DΞ threshold (3179-3191 MeV) and could be a bound state of DΞ. Wang et al [39] used the Bethe-Salpeter formalism to study the S-wave DΞ interaction, and they found two bound states, one isoscalar and one isovector, which could contribute to the 3188 MeV structure near the five new narrow Ω c states. Debastiani et al [34] and Liang et al [40] used an extension of the chiral unitary model to calculate the interactions between DΞ, D Ã Ξ,BΞ,B Ã Ξ plus other channels and obtained one zero-width state with J P ¼ 1=2 − , 3=2 − , which couples mostly to D Ã Ξ andB Ã Ξ, and another state with J P ¼…”
Section: Introductionmentioning
confidence: 99%